HUBUNGAN ANTARA ADAB SISWA DENGAN MOTIVASI GURU PAI DALAM MENGAJAR DI SMP PLUS JA-ALHAQ KOTA BENGKULU - Ezi Nurjanah Putri; Zulkarnain; Alimni (STKIP Subang, 2026)
Students’ etiquette is one of the important aspects of the educational process that can influence the learning climate and teachers’ motivation in teaching. Islamic Religious Education teachers play a strategic role in shaping students’ character; therefore, teacher motivation is essential to ensure that the learning process runs optimally. This study aims to determine the relationship between students’ etiquette and the teaching motivation of Islamic Religious Education teachers at SMP Plus Ja-Alhaq, Bengkulu City. This research employed a quantitative approach using a correlational method. The research population consisted of all ninth-grade students of SMP Plus Ja-Alhaq, totaling 21 students. A saturated sampling technique was applied, in which the entire population was used as the sample. Data were collected using a Likert-scale questionnaire. The results of the validity test indicated that all questionnaire items were valid, with calculated r-values greater than the r-table value (0.444). The reliability test yielded a Cronbach’s Alpha value of 0.978, indicating that the instrument was highly reliable. The Kolmogorov–Smirnov normality test showed a significance value of 0.060 > 0.05, suggesting that the data were normally distributed. The linearity test produced a significance value of 0.000 < 0.05, indicating a significant linear relationship. The simple regression analysis resulted in an F-value of 15.409 with a significance value of 0.000 < 0.05, leading to the acceptance of the alternative hypothesis (Ha). Based on the findings, it can be concluded that there is a significant relationship between students’ etiquette and the teaching motivation of Islamic Religious Education teachers. The better the students’ etiquette particularly in terms of politeness, discipline, and respect toward teachers the higher the teachers’ motivation in carrying out their teaching duties.